Potential effectiveness of parenteral nemonoxacin in the treatment of Clostridioides difficile infections: in vitro, ex vivo, and mouse studies - Lee, Ching-Chi; Yan, Xiang-Zhe; Wu, Hung-Tsung; Ko, Wen-Chien; Tsai, Pei-Jane; Hung, Yuan-Pin (Frontiers in Microbiology, 2024)
Introduction Antimicrobial therapy plays a crucial role in the management of CDI patients. However, the standard agent for treating CDIs is limited to oral fidaxomicin or vancomycin. For patients made nil by mouth, there is a clinically urgent and essential need to develop an intravenous antibiotic. Methods For C. difficile with the lowest MIC of nemonoxacin and vancomycin, the inhibitory effects were tested using the kinetic time-kill assay and ex vivo co-culture model. The effectiveness of nemonoxacin and vancomycin in inhibiting spore germination, the sporicidal activity, and the treatment of mice with CDIs were compared. Results For clinical isolates and laboratory strains, lower MICs of nemonoxacin against C. difficile than levofloxacin and ciprofloxacin were observed, even in those harboring point mutations in the quinolone-resistance determining region. Although nemonoxacin failed to suppress spore outgrowth and germination in C. difficile, it exhibited an effective inhibitory effect against C. difficile in the kinetic time-kill assay and the ex vivo co-culture model. Mice receiving intraperitoneal nemonoxacin had less weight loss, higher cecum weight, a longer colon length, and lower expression of the tcdB gene, compared with untreated mice. Notably, there were no significant differences observed in weight loss, cecum weight, colon length, or tcdB gene expression between mice treated with vancomycin and those treated with any dose of nemonoxacin. Similarly, no significant differences were found between mice receiving combination therapy of intraperitoneal nemonoxacin plus oral vancomycin and those treated with intraperitoneal nemonoxacin or oral vancomycin alone. Discussion The potential role of nemonoxacin, which can be administered parenterally, for treating CDIs was evidenced through the in vitro, ex vivo, and mouse models.